2006
DOI: 10.1016/j.molcel.2005.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Myosin VI Dimerizes and Moves Processively along Actin Filaments upon Monomer Clustering

Abstract: Myosin VI is a reverse direction actin-based motor capable of taking large steps (30-36 nm) when dimerized. However, all dimeric myosin VI molecules so far examined have included non-native coiled-coil sequences, and reports on full-length myosin VI have failed to demonstrate the existence of dimers. Herein, we demonstrate that full-length myosin VI is capable of forming stable, processive dimers when monomers are clustered, which move up to 1-2 mum in approximately 30 nm, hand-over-hand steps. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
155
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(181 citation statements)
references
References 18 publications
15
155
3
Order By: Relevance
“…This point is confirmed by ours and earlier data [7][8][9] . Thus, the geometrical relationship between the two lever arms should depend on the distance between the two heads after any given step, a point made previously by both groups 2,9 .…”
Section: Introductionsupporting
confidence: 93%
“…This point is confirmed by ours and earlier data [7][8][9] . Thus, the geometrical relationship between the two lever arms should depend on the distance between the two heads after any given step, a point made previously by both groups 2,9 .…”
Section: Introductionsupporting
confidence: 93%
“…Although myosin VI is a monomer in solution, it nevertheless can move processively along actin filaments with surprisingly long strokes 33 . Dimerization was found to be regulated by the clustering of myosin VI on the surface of its vesicular cargo 34 , reminiscent of the mechanism that was proposed for the kinesin UNC104 (REF. 35).…”
Section: Minus End (Plus End) Directionmentioning
confidence: 91%
“…Thus myosin VI can potentially fulfill a number of specialized cell biological functions (8-10). Paradoxically, although these functional features suggest that myosin VI is designed to work in cells as a dimer, myosin VI as isolated from cells is a monomer, and expressed full-length myosin VI is also monomeric (4,5,11).A number of cargo adaptor proteins that recruit myosin VI have been identified (8). For example, it has been demonstrated that optineurin is essential for myosin VI localization to the Golgi complex (12), and binds to a site within the globular tail of myosin VI.…”
mentioning
confidence: 99%
“…Thus myosin VI can potentially fulfill a number of specialized cell biological functions (8-10). Paradoxically, although these functional features suggest that myosin VI is designed to work in cells as a dimer, myosin VI as isolated from cells is a monomer, and expressed full-length myosin VI is also monomeric (4,5,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation